Identifying Differences in Consumer Attitudes towards Local Foods in Organic and National Voluntary Quality Certification Schemes - Hristo Hristov; Karmen Erjavec; Igor Pravst; Luka Juvančič; Aleš Kuhar (Foods, 2023)
As no study on attitudes towards local food has compared “organic” and national quality scheme consumer segments, this study aimed to provide further insights and clarifications on the issue of consumer segmentation in terms of trust towards organic food and food of selected quality perceived as local, along socioeconomic characteristics, and other important determinants of this complex interaction. The research examines consumers’ attitudes and perceptions related to two quality schemes for special Slovenian foods: “Organic”, which relates to production methods; and “Selected Quality”, which relates to quality attributes. The study focused on two segments of consumers, who exhibit a high level of trust towards the two quality schemes. Comparative analysis of the consumer segments looked for the potential differences with respect to their sociodemographic profiles, as well as to their understanding of the definition of local food, attitudes towards local food, trust in actors and institutions, and willingness to purchase local food. The study combined qualitative approaches and a quantitative survey with a general population sample. The results showed that both consumer groups have similar understandings of local food, with region-based interpretations outperforming country-based interpretations. The “Organic” group was more cosmopolitan and supportive of the local community, regardless of geographic proximity, than the “Selected Quality” group. Older consumers occupy a larger share of both segments, with professionals and individuals with higher incomes more likely to be in the “Organic” group and retirees and students more likely to be in the “Selected Quality” group. To increase the consumers’ interest in food with the “Organic” and “Selected Quality” schemes, more specific product propositions should be developed.